(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Scientific research is an important activity that helps health students develop skills and apply knowledge into practice. However, the rate of students participating in scientific research is still low due to many difficulties such as limitations in knowledge, time and funding. Objective: Describe the current status of scientific research participation and identify factors related to publishing scientific articles of students of the Institute of Preventive Medicine and Public Health - Hanoi Medical University in 2023. Research methods: Cross-sectional descriptive study on 236 students of the Institute of Preventive Medicine and Public Health - Hanoi Medical University in 2023. Data were collected through self-administered questionnaires, focusing on surveying the current status and factors related to students’ participation in scientific research. Results: 10.6% of students had participated in scientific conferences, with 4.2% being the lead author and presenter. 20 students contributed to at least 1 published domestic article and 5 students contributed to at least 1 published international article. Additionally, 11.1% of students were able to write articles independently without the support of their instructors. Notably, attending scientific research training courses was statistically associated with participation in published articles. . Conclusion: The participation rate of students in scientific research remains low. The university should regularly organize workshops to equip students with the necessary research skills.